IIUM2World: reaching out to the illiterates in rural Community - Md Hasim, Nur Nadiah; Ahmad Firdaus, Khadijah Hanis; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
This paper intends to propose a conceptual solution that provides an e-program for the community in the rural areas, which basically face illiteracy problems. With a proposed conceptual system of Quadruple Helix Model (QHM) which leverage four main actors namely: academia, industry, government, and citizen; also with the collaborative Network-of-Mosques (NoM), this project initiative aims to enhance the condition of the community in the rural areas of Malaysia by delivering such knowledge and virtues, mainly by teaching Malay and English language, also the Islamic knowledge to them through an e-program. Literature reviews were conducted to understand their conditions and environment. A Business Model Canvas (BMC) and Value Proposition Canvas (VPC) were created to highlight the main components in order to carry out this project. The authors conclude with suggestions of future work for next paper.